Learning on the fly with the analogical method - Zara Mehrnoosh; Sabrina Fusi (Firenze University Press, 2016)
Today in Italy 20-25% of students in primary school is reported to have difficulties with mathematical skills, although several researchers have noticed a man's natural predisposition towards numbers. In the light of this high number of reports becomes therefore necessary to reconsider the didactic context to better support the natural evolution of numerical and mathematical cognition from early childhood. The following article presents the analogical method developed by Camillo Bortolato: non-conceptual didactic path focused on semantic process, subitizing and mental math.   Apprendere al volo con il metodo analogico Ad oggi in Italia il 20-25% degli alunni nella scuola primaria viene segnalato per difficoltà nel calcolo, nonostante diversi ricercatori abbiano evidenziato una naturale predisposizione dell'uomo verso la numerosità. Alla luce di questo elevato numero di segnalazioni diviene necessario ripensare il contesto didattico per sostenere al meglio e fin dalla prima infanzia la naturale evoluzione della cognizione numerica e di calcolo. Nel seguente articolo viene presentato il metodo analogico di Camillo Bortolato, un percorso didattico non concettuale attento ai processi semantici, al ruolo del subitizing e del calcolo a mente.